2023
DOI: 10.1002/maco.202213671
|View full text |Cite
|
Sign up to set email alerts
|

Study on the corrosion‐wear behavior of Ni67.57Cr15.59Fe2.83C0.6Si3.98B3.47O0.045Mo2.97Co2.94 nickel alloy coating prepared by high velocity oxygen fuel spraying

Abstract: Ni‐based alloy coatings are sprayed on 304 stainless steel substrates using a high velocity oxygen fuel spraying (HVOF) method. The corrosion‐wear behavior was analyzed using a “block on ring” corrosion‐wear system. This study mainly discusses the effect of different applied potentials on corrosion and wear interaction using scanning electron microscopy, transmission electron microscopy and X‐ray photoelectron spectroscopy (XPS). The results show that as the applied potential increases, the weight loss and cor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 38 publications
0
0
0
Order By: Relevance
“…As mentioned previously in this work, the corrosion resistance of the coating will be affected by the alloy compositions and the original defects in the coating or the coating quality. It is reported that Ni-based coatings are also widely used in marine environments [53][54][55][56][57][58][59][60][61]. Referring to the open literature, the corrosion resistance and hardness of the investigated amorphous coating are compared to those of the Ni-based coatings, as listed in Table 3.…”
Section: Discussionmentioning
confidence: 99%
“…As mentioned previously in this work, the corrosion resistance of the coating will be affected by the alloy compositions and the original defects in the coating or the coating quality. It is reported that Ni-based coatings are also widely used in marine environments [53][54][55][56][57][58][59][60][61]. Referring to the open literature, the corrosion resistance and hardness of the investigated amorphous coating are compared to those of the Ni-based coatings, as listed in Table 3.…”
Section: Discussionmentioning
confidence: 99%